2003
DOI: 10.1542/peds.112.2.e153
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cytomegalovirus Infection in Twin Pregnancies: Viral Load in the Amniotic Fluid and Pregnancy Outcome

Abstract: Human cytomegalovirus (CMV) is the most common cause of viral intrauterine infection and fetal damage largely attributable to maternal primary infection. Most cases of congenital CMV infection in twins reported in the literature involved only 1 twin. We assessed the validity of polymerase chain reaction (PCR) and quantitative PCR on amniotic fluid (AF), at 21 to 22 weeks' gestation and at least 6 to 8 weeks after seroconversion, to predict the outcome of newborns in twin pregnancies. Two pregnant women with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 35 publications
1
73
1
5
Order By: Relevance
“…In contrast to the findings of Lazzarotto et al (19,20), Gouarin et al (13), and Guerra et al (15), our study could not demonstrate a correlation between the CMV viral load in AF and the outcome for the fetus. Instead, in most of the nonterminated pregnancies, the CMV viral load in AF seemed to be related to the time during the pregnancy when the amniocentesis was performed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the findings of Lazzarotto et al (19,20), Gouarin et al (13), and Guerra et al (15), our study could not demonstrate a correlation between the CMV viral load in AF and the outcome for the fetus. Instead, in most of the nonterminated pregnancies, the CMV viral load in AF seemed to be related to the time during the pregnancy when the amniocentesis was performed.…”
Section: Discussioncontrasting
confidence: 99%
“…The value of the results of quantitative PCR for CMV in AF as a prognostic indicator of symptomatic congenital infection is even more controversial. Some authors have found that a high CMV viral load in AF is associated with a high risk of symptomatic infection in the fetus (13,15,19,20). Others, however, failed to demonstrate such an association (27,29,36), whereas still others proposed a possible association between the viral load in AF and the gestational age at the time of amniocentesis (13,29).…”
mentioning
confidence: 99%
“…[7][8][9] Although the fetus can be affected by CMV during all trimesters of pregnancy the risk of transplacental infection in first trimester reaches up to 40%. [10][11][12] Of these babies 10 to 15% are acutely symptomatic at birth, and among these infants up to 80% will have serious sequelae. 2,3 Clinical presentation of cCMV can involve all systems that are commonly explained by the spread of CMV virus during fetal viremia and subsequent T-cell response to CMV antigens expressed on the interstitial cells of different organs (liver, brain, lungs, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Lazarotto et al studied three sets of multiple pregnancies showed that CMV DNA in amniotic fluid of at least 1000 genome equivalents gave a 100% chance of predicting fetal infection. 20 Higher viral loads (>100,000 genome equivalents) predicted the development of symptomatic infections. A similar study of 68 pregnancies diagnosed with maternal CMV also analyzed CMV viral load in amniotic fluid as a diagnostic tool for the prediction of congenital CMV infection.…”
Section: Prenatal Diagnosismentioning
confidence: 99%